The long history of rich fens supports persistence of plant and snail habitat specialists - Peterka, Tomáš; Tichý, Lubomír; Horsáková, Veronika; Hájková, Petra; Coufal, Radovan; Petr, Libor; Dítě, Daniel; Hradílek, Zbyněk; Hrivnák, Richard; Jiroušek, Martin; Plášek, Vítězslav; Plesková, Zuzana; et al. (Biodiversity and conservation, 2022)
Increasing evidence for the effects of Holocene history on modern biotic communities suggests that current explanations of community patterns and conservation strategies require revisiting. Here we focused on Central European rich fens that are at high risk among mire habitats because of their relatively low environmental stability, and hence sensitivity to successional shifts. At each of 57 study sites, inventory of specialist species of bryophytes, vascular plants and land snails, measurements of local environmental conditions, area, and radiocarbon dating were conducted. We used Moran’s I spatial autocorrelation, multiple linear regression models, MDS, db-RDA, and null models to identify drivers of species richness and occurrence. We tested the importance of site age and historical metacommunity dynamics expressed by regional age of the habitat for the diversity of three taxonomic groups of fen organisms differing in dispersal and life history strategies. The richness of specialist species was affected by local environmental conditions and area in all three groups, but the effect of regional age was significant and positive for vascular plants and snails, once the effect of fen area was set as a covariable. We identified 11 species significantly associated with ancient fens independently of site area and pH effects; this group includes species currently considered to be umbrella species in European habitat conservation (the moss Hamatocaulis vernicosus and the snail Vertigo geyeri ). The effect of fen age per se on the communities of specialists calls for the incorporation of age into conservation schemes. Restoration or de novo construction of peat-forming fens cannot compensate for a loss of ancient fens.